1982
DOI: 10.1080/03015521.1982.10427873
|View full text |Cite
|
Sign up to set email alerts
|

European hybrid asparagus cultivars in New Zealand

Abstract: Six asparagus cultivars were compared with Mary Washington 500W for yield, early and late production, quality, plant survival, and sex ratio over 4 harvest seasons at Lincoln, New Zealand. Accumulated total yields of 18.2, 17.7, 16.0, 14.1, 10.5, and 10.3 t/ha from Larac, Limbras Early, Minerve, Limbras Maincrop, Diane, and Junon respectively were significantly higher than from MW500W (6.8 t/ha). Quality of harvested spears was as good as or better than MW500W. Larac and Minerve produced higher early yields th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…By 1985, trials in New Zealand had identified hybrids in this range capable of yielding from 40 to 200% more processing grade ( 180 mm long) spears than the two widely planted, open-pollinated cultivars-'Mary Washington 500W' and 'New Zealand Beacon' (Bussell et al 1981;Falloon & Nikoloff 1982;Busselletal. 1985).…”
Section: Introductionmentioning
confidence: 98%
“…By 1985, trials in New Zealand had identified hybrids in this range capable of yielding from 40 to 200% more processing grade ( 180 mm long) spears than the two widely planted, open-pollinated cultivars-'Mary Washington 500W' and 'New Zealand Beacon' (Bussell et al 1981;Falloon & Nikoloff 1982;Busselletal. 1985).…”
Section: Introductionmentioning
confidence: 98%
“…Like all crops, asparagus growth is complex and primarily driven by energy capture (photosynthesis) ( Bai and Kelly, 1999 ; Faville et al., 1999 ), with the assimilated carbon stored in the fleshy storage roots. Asparagus genetics is also important since cultivars are often selected for unique environments ( Lin, 1979 ; Falloon and Nikoloff, 1982 ; Garrison et al., 1999 ; Motoki et al., 2008 ). There is some evidence of cultivar differences in photosynthesis and yield ( Benson and Takatori, 1980 ; Woolley et al., 1996 ; Bai and Kelly, 1999 ; Faville et al., 1999 ; Guo et al., 2002 ).…”
Section: Introductionmentioning
confidence: 99%